Fruit flies actively restart their circadian clock by proactively shaping their environment - Angelica Coculla; Luis Garcia Rodriguez; Maite Ogueta; Ralf Stanewsky (Science, 2026)
Circadian clocks provide adaptive advantages, enabling organisms to adjust their physiology and behavior to daily environmental changes on Earth. Here, we show that fruit flies prefer a temporally organized life. Because of light-induced degradation of the core circadian clock protein Timeless, constant illumination stops the circadian clock and leads to arrhythmic locomotor activity. When given the choice to move between dark and illuminated areas in a constant light environment, flies were able to maintain, or even regain, rhythmic behavioral patterns. These self-inflicted rhythms were accompanied by molecular rhythms in clock neurons known to drive behavioral rhythms. Behavioral rhythmicity was correlated with improved sleep quality compared with that of arrhythmic flies, demonstrating an immediate benefit of choosing to live under circadian clock control.